Lychnophora pinaster in endangered campos rupestres: phenolic compounds and population ecogeography - Dos Santos, Dayane G. P. O. [UNESP]; Corrêa, Lilian C.; Silva, Júlio C. R. L. [UNESP]; Gomes, Jordany A. O. [UNESP]; Semir, João; Monge, Marcelo; Ming, Lin C. [UNESP]; Martins, Ernane R.; Zucchi, Maria I.; Hantao, Leandro W.; Sawaya, Alexandra C. H. F.; Marques, Marcia Ortiz M. (FapUNIFESP (SciELO), 2023)
Lychnophora pinaster, known as arnica-mineira, is endemic to campos rupestres, at risk of extinction. The present study aimed to characterize the ecogeography and phenolic constituents of 11 L. pinaster populations collected in the mesoregions North, Jequitinhonha, Metropolitan of Belo Horizonte and Campos das Vertentes in the state of Minas Gerais, Brazil. Phenolic constituents were identified and quantified by Ultra-high performance liquid chromatography-mass spectrometry. Lychnophora pinaster occurs in sites at high altitude (700 and 1498 m), annual rainfall of up to 1455 m, soils with low fertility and predominantly loamy texture. Therefore, it can be considered tolerant to acidic soils, with low availability of nutrient. The most abundant substances in all populations were vitexin (18 – 1345 ng/g) and chlorogenic acid (60 – 767 ng/g). The 11 populations formed four groups in relation to the phenolic constituents, with group 1 consisting of the populations of the North Mesoregion (GM, OD) and Jetiquinhonha (DIMa), group 2, the Metropolitan of Belo Horizonte (SRM, NLSC, SM, RPS, CTRA), group 3, the North Mesoregion (ODMa and DI), and group 4, the Campos das Vertentes (CC). Among the populations, only those from the Metropolitan of Belo Horizonte showed correlation of soil properties with phenolic constituents.
Keywords: arnica-mineira; Asteraceae; flavonoids; medicinal plants; soil